Designing priority databases for QMS according to ISO 9001: 2015 standard - Miletić, Ljiljana Z.; Jovanović, Aca D.; Jovanović, Filip P.; Buha, Vesna V. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The international ISO 9001:2015 standard for quality management system (QMS) is widely implemented in this country, especially in business organisations and in public administration. The Standard was created in 1987; it was revised and amended in 1994, 2000 and 2008, the latest amendments being of the largest scope. Compared to the previous ISO 9001:2008 standard, this standard does not require a complicated manual to be devised: instead of six, it needs no documented procedures now and only 18 prescribed reports are required in comparison with 21 in the previous version. The organisations that have already certified their standards to comply to the earlier ISO 2001:2008 standard have to adopt the new standard now, and no later than 2018. One of the greatest problems in this transition is designing the required databases necessary for the practical implementation of the new standard. The solution proposed by the authors is a general model with six priority databases: Documented information database; Measuring, control and testing equipment database; Qualified personnel  database; Complaints on process output nonconformity database; Costs of process output nonconformity database and Plant and work equipment maintenance database.
Keywords: priority data bases; Quality management system; standard ISO 9001; 2015